Proposed Cardiac End Points for Clinical Trials in Immunoglobulin Light Chain Amyloidosis: Report From the Amyloidosis Forum Cardiac Working Group. (25th March 2022) - Maurer, Mathew S.; Dunnmon, Preston; Fontana, Mariana; Quarta, Cristina Candida; Prasad, Krishna; Witteles, Ronald M.; Rapezzi, Claudio; Signorovitch, James; Lousada, Isabelle; Merlini, Giampaolo
Abstract : Immunoglobulin light chain amyloidosis is a rare, multisystemic, phenotypically heterogenous disease affecting cardiovascular, renal, neurological, and gastrointestinal systems to varying degrees. Its underlying cause is a plasma cell dyscrasia characterized by misfolding of monoclonal immunoglobulin light chains which leads to aggregation and deposition of insoluble amyloid fibrils in target organs. Prognosis is primarily dependent on extent of cardiac involvement and depth of hematologic response to treatment. To facilitate development of new therapies, a public-private partnership was formed between the nonprofit Amyloidosis Research Consortium and the US Food and Drug Administration Center for Drug Evaluation and Research. In 2020, the Amyloidosis Forum launched an initiative to identify novel/composite end points and analytic strategies to expedite clinical trials for development of new therapies for the primary hematologic disorder and organ system manifestations. Specialized working groups identified organ-specific end points; additional working groups reviewed health-related quality of life measures and statistical approaches to data analysis. Each working group comprised amyloidosis experts, patient representatives, statisticians, and representatives from the Food and Drug Administration, the UK Medicines and Healthcare Products Regulatory Agency, and pharmaceutical companies. This review summarizes the proceedings and recommendations of the Cardiac Working Group. Using a modified Delphi method, the group identified, reviewed, and prioritized cardiac end points relevant to immunoglobulin light chain amyloidosis in the context of an antiplasma cell therapy. Prioritized cardiovascular end points included overall survival, hospitalization, N-terminal pro-B-type natriuretic peptide level, 6-minute walk test, Kansas City Cardiac Questionnaire, and cardiac deterioration progression-free survival. These recommended components will be further explored through evaluation of clinical trial datasets and formal guidance from regulatory authorities.